A case of Grover’s disease - N.V. Zilberberg; M.M. Kokhan; A.I. Polishchuk; O.G. Rimar; Y.V. Kashcheeva; N.K. Levchik; V.A. Iordan (Russian Journal of Clinical Dermatology and Venereology, 2026)
Grover’s disease (GD) is an acantholytic dermatosis with a transient, persistent, or oligosymptomatic course, most often affecting Caucasian men; the etiology of the disease remains unclear. GD is characterized by polymorphism of clinical manifestations, including a papulovesicular rash accompanied by itching and the development of secondary elements in the form of crusts. It may resemble various chronic dermatoses, which requires the dermatovenereologist to be attentive in the differential diagnosis of this disease. The final diagnosis is established on the basis of histopathological studies of skin biopsy samples in the presence of a typical morphological picture of this disease. Patient management is primarily symptomatic and includes systemic antihistamines and topical glucocorticosteroids to relieve pruritic symptoms; in refractory cases, systemic glucocorticosteroids, retinoids, and phototherapy may be used. We present a case of a 24-year-old male patient with recurrent GD, clinical photographs of skin lesions in various anatomical locations, as well as the results of a histopathological examination of a skin biopsy from the lesion. The diagnosis of GD was established based on an analysis of clinical and pathomorphological data. This clinical case may be of interest due to the relative rarity of GD diagnosis in clinical practice and will be useful for practicing dermatovenereologists to gain experience in the differential diagnosis of rare dermatoses.